A chemical study of Luffa cylindrica (Linn.) Roemer with special emphasis on its saponin - Mendoza, Amparo S. 1918-
PURPOSE: To conduct a chemical study on Luffa cylindrica (Linn.) Roemer with special emphasis on its saponin. In a previous study the crystalline principle C30H4808, was also the subject of a chemical investigation. The present work is a continuation of studies on Luffa cylindrica (Linn.) Roemer being undertaken in the College of Pharmacy. PROCEDURE: A crystalline saponin melting at 268-270(degrees C) has been isolated from Luffa cylindrica (Linn.) Roemer. Some physical and chemical properties of the saponin were determined. Elementary analysis were carried out. Spectroscopic examinations were made. The saponin formed a cholesteride melting at 135-138(degrees C). The saponin was hydrolyzed into a sapogenin melting at 283-285(degrees C) and a sugar component. The hemolytic index, the foam index and the fish index of the saponin were determined. The minimum fatal dose in frogs were also determined. A pharmacological test on the dog was carried out under the direction of Dr. Romulo Guevara of the Department of Pharmacology, College of Medicine, U.P. AMOUNT OF TIME DEVOTED TO RESEARCH: about 10 months. DEGREE OF SUPERVISION: The candidate was given ample freedom in the investigation. Conferences and consultations were held once in a while. RESULTS OF THE INVESTIGATION: A crystalline saponin melting at 268-270(degrees C). [α]28(degrees) D = .25(degrees) was isolated from Luffa cylindrica (Linn.) Roemer. Some physical and chemical properties of the saponin were determined. Elementary analysis of the saponin gave: C = 50.80%, H = 8.18%, residue = 9.32%. Spectroscopic examination gave negative results for the presence of sodium, potassium, calcium, lithium, barium, magnesium, strontium, lead and zinc. The saponin formed a crystalline cholesteride melting at 135-138(degrees C). On hydrolysis, the saponin is split into a sapogenin melting at 283-285(degrees C), crystalline in the form of feathery needle-like crystals and a sugar component giving positive results with Fehling's test. Using dog's blood, the hemolytic index was found to be 1:27,000. The foam index was 1:7,000. The determination of the fish index, using mosquito fishes gave 1:33,000. The minimum fatal dose was 0.06 mgs. per gram of body weight. Pharmacological tests were conducted under the direction of Dr. Romulo Guevara. Administration of 30 mgs. per gm. of body weight on a dog, resulted in an increase of pulse rate, increase of urination, slowing up of breathing, dilatation of the pupils of the eye and slight decrease of rectal temperature.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1941.
Keywords: Plants -- Analysis; Saponins; Luffa aegyptiaca